EKONOMI KREATIF MELALUI INOVASI PENGOLAHAN BAWANG MERAH UNTUK MENINGKATKAN PERTUMBUHAN EKONOMI DESA - Syaifatul Jannah (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2022)
Creative economy is a new economic concept to generate creative ideas from an opportunity or asset. The creative economy is one of the strategies in increasing village economic growth. Through the creative economy, brilliant ideas will be born to create something new with high selling value. Likewise, Tambak village is the target of this community empowerment activity. Tambak Village with its superior asset, namely shallots, will increase village economic growth through new innovations from processing shallots into creative products with selling value. To achieve this goal, the author uses the Asset Based Community Development (ABCD) method. This method was developed from the assets owned, not based on the problem. With the ABCD method, the author creates a creative economy from the village's superior assets, namely the innovation of processing shallots into products that are worth selling. The result of this activity is the launching of BAMECRIS and LAWANG products from processed shallots which are well received, and have received many orders from people outside the village.